1974
DOI: 10.1007/bf01869987
|View full text |Cite
|
Sign up to set email alerts
|

The stimulation of chloride transport by prostaglandins and their interaction with epinephrine, theophylline, and cyclic AMP in the corneal epithelium

Abstract: Summary. Prostaglandins (El, E 2 and F2~ ) stimulated the chloride transport of the frog corneal epithelium with maximal effects at 10 -5 M in the aqueous side. This stimulation does not occur in Cl-free solutions and the net 36C1 flux increased proportionally to the short-circuit current. Polyphloretin phosphate (PPP) and diphloretin phosphate (DPP) inhibited the response if added within 3 rain before PGE 1. The maximal response to epinephrine 10-SM and dibutyryl cyclic AMP 10-3M was not changed by further ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…To our knowledge the drugs we used to enhance the wound-generated EF altered only the TCPD and did so by different mechanisms. PGE2 enhances chloride efflux, aminophylline and ascorbic acid inhibit phospodiesterase breakdown of cAMP, which also enhances Cl -efflux ( ., 1974;Buck and Zadunaisky, 1975) and AgNO3 increases both early Na + uptake and later Cl -efflux (Klyce and Marshall, 1982). Similarly, we chose drugs that suppressed the woundgenerated EF, by reducing the TCPD in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge the drugs we used to enhance the wound-generated EF altered only the TCPD and did so by different mechanisms. PGE2 enhances chloride efflux, aminophylline and ascorbic acid inhibit phospodiesterase breakdown of cAMP, which also enhances Cl -efflux ( ., 1974;Buck and Zadunaisky, 1975) and AgNO3 increases both early Na + uptake and later Cl -efflux (Klyce and Marshall, 1982). Similarly, we chose drugs that suppressed the woundgenerated EF, by reducing the TCPD in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…rabbit ileum, rabbit gall-bladder (Frizzell, Dugas & Schultz, 1975), rat colon (Binder & Rawlins, 1973) 60-90 Q cm2, guinea-pig gallbladder (Saverymuttu & Wood, 1977), and fly salivary gland (Prince & Berridge, 1973) to secretagogues differs from the response of a number of tight epithelia, e.g. rabbit colon (Frizzell, Koch & Schultz, 1976) 220-270 Q cm2, guinea-pig seminal vesicle (Levine, Rinaldo & Schultz, 1976), rabbit cornea (Beitch, Beitch & Zadunaisky, 1974), and frog skin (Cuthbert & Painter, 1968). In the latter group of tight epithelia, the secretagogues have no inhibitory effect on either net or unidirectional transepithelial Na+ fluxes, indeed they may stimulate Na+ absorption in frog skin, whilst causing marked increases in the short-circuit current due to stimulated Cl-secretion.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a decreased transepithelial conductance is not the invariable response of all epithelia following exposure to secretagogues. Frizzell, Koch & Schultz (1976) with rabbit colon and Beitch, Beitch & Zadunaisky (1974) with rabbit cornea have shown that cyclic AMP increases active Cl-secretion, short circuit current and also transepithelial conductance in both these 'tight' epithelia. More recently Frizzell (1977) has shown that Ca2+ ionophore A 23187 causes increased short-circuit current due to active Cl-secretion, accompanied by increased electrical conductance across rabbit colon; whereas Bolton & Field (1977) have shown that A 23187 increases short circuit current, and Cl-secretion but decreases transepithelial conductance across rabbit ileum.…”
Section: Introductionmentioning
confidence: 97%